2015
DOI: 10.1177/1753425915587130
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in TLR9 but not in TLR5 increase the risk for duodenal ulcer and alter cytokine expression in the gastric mucosa

Abstract: Colonization of the gastric mucosa by Helicobacter pylori can lead to peptic ulcer and gastric adenocarcinoma. TLRs are signaling receptors involved in the recognition of microorganisms, and polymorphisms in their genes may influence the innate and adaptive immune response to H. pylori, affecting the clinical outcomes of the infection. We assessed the association between single nucleotide polymorphisms in TLR9 and TLR5 and gastroduodenal diseases. All patients were genotyped by allelic discrimination in region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
(41 reference statements)
2
18
0
2
Order By: Relevance
“…The authors of a previous study reported that the TLR9 gene causes an intracellular receptor signal cascade, and thus evokes nuclear transcription factors resulting in the production of pro-and anti-inflammatory cytokines (Hemmi et al, 2000). The authors of previous studies have reported that TLR9 gene polymorphisms are associated with the development of several inflammatory diseases (Bharti et al, 2014;Berenson et al, 2015;Trejo-de la O et al, 2015;Wen et al, 2015;Wujcicka et al, 2015). Bharti et al (2014) conducted a study in a Chinese population and assessed the association between TLR9 polymorphisms and pulmonary tuberculosis; they found that the TLR9 rs187084 polymorphism was associated with reduced risk of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of a previous study reported that the TLR9 gene causes an intracellular receptor signal cascade, and thus evokes nuclear transcription factors resulting in the production of pro-and anti-inflammatory cytokines (Hemmi et al, 2000). The authors of previous studies have reported that TLR9 gene polymorphisms are associated with the development of several inflammatory diseases (Bharti et al, 2014;Berenson et al, 2015;Trejo-de la O et al, 2015;Wen et al, 2015;Wujcicka et al, 2015). Bharti et al (2014) conducted a study in a Chinese population and assessed the association between TLR9 polymorphisms and pulmonary tuberculosis; they found that the TLR9 rs187084 polymorphism was associated with reduced risk of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bharti et al (2014) conducted a study in a Chinese population and assessed the association between TLR9 polymorphisms and pulmonary tuberculosis; they found that the TLR9 rs187084 polymorphism was associated with reduced risk of pulmonary tuberculosis. Trejo-de la O et al (2015) conducted a study in a Mexican population and revealed that the A allele of TLR9+2848 was associated with increased risk of duodenal ulcers, and modified the expression of inflammatory cytokines in the gastric mucosa. Wen et al (2015) reported that TLR9+2848 had a correlation with systemic lupus erythematosus in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…We used samples from multiple studies to represent a wide range of Latin American populations from high‐ and low‐risk of GC, and of the whole spectrum of lesions from gastritis to GC. Details concerning eligibility, recruitment, data and sample collection, endoscopic examination and pathological diagnoses of each study have been published elsewhere 9,14‐20 . Subjects were at least 30 years old, and recruited from four countries in Latin America, with contrasting risk for GC, Venezuela (Tachira province) with high‐risk, Colombia with five cities representing both high‐ and low‐risk areas, and two countries with lower risk, Mexico (two hospitals in Mexico City) and Paraguay (two hospitals in Asunción City) in a varied period from the early 1990s to early 2000s; however, in each site recruitment time spanned no more than 3 years and all disease groups were collected within the same time period.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, TLR9 SNPs have been implicated in increasing gastric cancer risk (Hold et al 2009; Wang et al 2013; Trejo-de la et al 2015). Given the highly established relationship between H. pylori and gastric cancer, we and others have sought to determine the effects of H. pylori on TLR9-mediated responses and its possible implications in gastric carcinogenesis.…”
Section: H Pylori/tlr9 Interactionsmentioning
confidence: 99%